AN ANALYSIS OF STELLA'S AND WILL'S LOVE LANGUAGE AND FREUDIAN TRIPARTITE IN in “FIVE FEET APART” FILM - Mulyadi, Mulyadi (Institut Seni Indonesia Yogyakarta, 2024)
The phenomenon that leads to the creation of this research is the implementation of love language in the “Five Feet Apart” film, and the inner workings of the three Freudian elements of the mind through the implementation of love language. This research has the objective toanalyzethe Freudian Tripartite using the framework of love languages, aiming to comprehend the personalities of characters in the film